A study on factor that influence online shopping in Malaysia - Ramlan, Rohaizan (2011)

(untitled)
Online shopping is a process in which buy goods or services through the Internet. With large of consumer using Internet for online shopping, it is not clear what drives them to shop online (Monsure et al., 2006) and studies regarding consumer behavior towards online shopping in the Malaysian environment is still limited number (Haque and Khatibi, 2006). Thus, this study objective is to identify dominant factor that influences consumers to buy online. Purposive sampling method was performed in the selection of sample. These items were empirically tested by data collected from consumer using internet for online shopping. Findings showed that usefulness factor is the most dominant followed by ease of use and enjoyment. In conclusion, consumers in Malaysia believe, with online shopping, shopping time may reduce and online shopping would make their life easier. They are also concerned about privacy, trust and disclosing personal information when dealing with online shopping.